The Impacts of Different Types of Radiation on the CRT and PDL1 Expression in Tumor Cells Under Normoxia and Hypoxia - Huang, Yangle; Huang, Qingting; Zhao, Jingfang; Dong, Yuanli; Zhang, Lijia; Fang, Xumeng; Sun, Pian; Kong, Lin; Lu, Jiade Jay (Frontiers in Oncology, 2020)
Introduction: Hypoxia is a hallmark of cancer which may contribute to an immunosuppressive microenvironment and promote radioresistance. High linear energy transfer (LET) radiation is considered to be able to overcome the negative effects of hypoxia. However, the anti-tumorigenic effects induced by low or high LET radiation have not been fully elucidated. This study aimed to compare the effects of different types of radiation on the immune response, particularly the impact on calreticulin (CRT) and programmed cell death ligand 1 (PDL1) expression. Methods: Four human tumor cell lines were investigated in this study. Cells in normoxic and hypoxic groups were irradiated with 4Gy (physical dose) photon, proton, and carbon-ion radiation, respectively. The expression of CRT and PDL1 were detected 48h after irradiation, and the median fluorescence intensities (MFI) were compared by flow cytometry. Meanwhile, the radiosensitivity of tumor cells in each group were also compared by colony formation assays and flow cytometry. Results: All types of radiation could significantly inhibit the colony formation of tumor cells under normoxia. However, the efficacy of photon and proton radiation were impaired under hypoxia. Carbon-ion radiation could still inhibit colony formation. The percentage of viable cells after irradiation was higher under hypoxia compared with those under normoxia. The CRT expression under normoxia was significantly increased after radiation. Carbon-ion radiation enhanced CRT expression compared to photon and proton radiation. Conversely, under hypoxia, the CRT expression level was significantly upregulated at baseline (0Gy). Radiation could not increase the expression further. PDL1 expression was also significantly increased by radiation under normoxia in all cell lines except the Ln18 cell line. Carbon-ion radiation induced the most significant increase. Under hypoxia, the PDL1 expression level was also upregulated at baseline and radiation could not increase expression further. Conclusion: Tumor cells were resistant to photon and proton, but sensitive to carbon-ion radiation under hypoxia. Carbon-ion radiation could induce the highest CRT and PDL1 expression under normoxia. However, under hypoxia, radiation could not further enhance the high baseline expression of CRT and PDL1.